Proposed Strategic Mandates for Ontario Universities: An Organizational Theory Perspective - Buzzelli, Michael D.; Allison, Derek J. (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2017)
This paper presents an empirical analysis of the Ontario-led strategic mandate agreement (SMA) planning exercise. Focusing on the self-generated strategic mandates of five universities (McMaster, Ottawa, Queen’s, Toronto, and Western), we asked how universities responded to this exercise of strategic visioning? The answer to this question is important because the SMA process is unique in Ontario, and universities’ responses revealed aspects of their self-understanding. We adopted an organizational theory approach to understand the structure and nature of universities as organizations and explored how they might confront pressures for change. Analysis of the universities’ own proposed strategic mandates found elements of both conformity and striking differentiation, even within this sample of five research-intensive university SMAs. Directions for further work on this planning exercise and on higher education reform more generally are discussed.